Fresh Water Fish Intake And Dishes Preferences Among Local Community: A Preliminary Study Of Tourists attraction in traditional dishes for homestay Kampung Batu Ring, Beng, Lenggong, Perak - Che Dah, Farhana; Abdul Hamid, Norsuhana; Hanoon N. A , Norfarizan (2013)
Local foods is a vital element that helping and creating a sense of ‘place’ and heighten destination appeal. Local foods produce adds authenticity to the tourists for sharing experience and attract them to come to those place. Traditional food or local food is a parts of variety culture in Malaysia. It shows that the local community has its own uniqueness. Therefore it should be opened and sharing together either between the local community from other states or from the tourist views for attractions the places. An objective of the study were ; (1) To identify the type of freshwater fish intake, (2) To determine dishes preference using freshwater fish among villagers at Homestayed Kampung Batu Ring, Beng, Lenggong. The study was conducted through questionnaires to 25 respondents in the village. The result showed that common freshwater fish consumed are Tengalan (Puntius wool), Loma (Thynnichthys thynnoides), Terbol (Osteochilus hasselti) and others fish such as Catfish, Tilapia, Kaloi, Baung and Patin. The most popular fresh water fish is responds for Tengalan fish. This fish when cooked with coconut gravy (masak lemak) is the most preference dishes indicated by respondents. Therefore, fresh water fish and traditional dishes that already exist there and has been a natural culture among villagers shall point out for promoting Lenggong city for tourism such as homestay program. These finding is important in branding Lenggong as a World Heritage Site.